Chronic Kidney Failure Provokes the Enrichment of Terminally Differentiated CD8+ T Cells, Impairing Cytotoxic Mechanisms After Kidney Transplantation - Leonhard, Jonas; Schaier, Matthias; Kälble, Florian; Eckstein, Volker; Zeier, Martin; Steinborn, Andrea (Frontiers in Immunology, 2022)
Chronic kidney failure (KF) provokes the development of immune senescent CD8+ cytotoxic T cells, affecting the occurrence of graft rejection, viral infections, and malignancies after kidney transplantation. In this study, we analyzed the impact of KF, subsequent dialysis treatment, and kidney transplantation on the differentiation of CD8+CD31+CD45RA+CCR7+ recent thymic emigrant (CCR7+ RTE) Tregs/Tresps into CD8+CD31-CD45RA- memory (CD31- memory) Tregs/Tresps and its effect on the release of cytokines, Fas receptor, Fas ligand as well as cytotoxic mediators by naïve, central memory (CM), effector memory (EM), and terminally differentiated effector memory (TEMRA) Tresps. We found that normal age-dependent differentiation of CD8+ Tregs/Tresps generally differs in the way that TEMRA cells only arise in Tresps. Compared to healthy controls, KF patients revealed an age-independently decreased frequency of CCR7+ RTE Tregs/Tresps, but increased frequencies of CCR7+ MN Tregs/Tresps and CD31- memory Tregs/Tresps, suggesting an increased differentiation via CD31+CD45RA- memory (CD31+ memory) Tregs/Tresps into CD31- memory Tregs/Tresps. Intensified differentiation via CD31+ memory Tresps increased the emergence of apoptosis-resistant CM Tresps with strong Fas ligand-mediated cytotoxicity. CCR7+ RTE Tresp proliferation generated TEMRA Tresps, secreting high levels of cytotoxic mediators. In dialysis and transplant patients, CD31+ TEMRA Tregs/Tresps accumulated, proposing an impaired CCR7+ RTE Treg/Tresp differentiation via CD31+ memory Tregs/Tresps into CD31- memory Tregs/Tresps. Increased percentages of CD31- TEMRA Tresps, but not of CD31- TEMRA Tregs, were observed in all patient groups, indicating impaired proliferation of CCR7+ RTE Tresps, but not of CCR7+ RTE Tregs, into CD31- memory Tregs/Tresps. In transplant patients, CCR7+ RTE Tregs accumulated, while frequencies of CCR7+ RTE Tresps were decreased, suggesting that the immunosuppressive therapy only prevented excessive CCR7+ RTE Treg differentiation but not that of CCR7+ RTE Tresps. Presumably, this caused the accumulation of TEMRA Tresps with decreased release of cytotoxic mediators, such as perforin. In conclusion, we propose that chronic KF affects both the differentiation of CD8+ Tregs and CD8+ Tresps. However, the immunosuppressive therapy after transplantation may successfully prevent increased Treg differentiation but not sufficiently that of Tresps. Therefore, the risk for graft rejection may be reduced, while the susceptibility for infections and malignancies may be increased in these patients.